Living with a Unilateral Mastectomy Defect: A Utility Assessment and Outcomes Study - Sinno, Hani; Izadpanah, Ali; Vorstenbosch, Joshua; Dionisopoulos, Tassos; Ibrahim, Ahmed M.S.; Tobias, Adam M.; Lee, Bernard T.; Lin, Samuel J. (Journal of Reconstructive Microsurgery, 2014)
Background The gold standard for the treatment of breast cancer includes mastectomy surgery. Our goal was to quantify the health state utility assessment of living with unilateral mastectomy.Methods The visual analogue scale (VAS), time trade-off (TTO), and standard gamble (SG) were used to obtain utilities for unilateral mastectomy, monocular blindness and binocular blindness from a prospective sample of the general population and medical students.Results All measures (VAS, TTO, SG) for unilateral mastectomy (0.75 SD 0.17, 0.87 SD 0.14, and 0.86 SD 0.18, respectively) of the 140 volunteers were significantly different from the corresponding scores for monocular (0.61 SD 0.18, 0.84 SD 0.17, and 0.84 SD 0.18, respectively) and binocular blindness (0.38 SD 0.17, 0.67 SD 0.24, and 0.69 SD 0.23, respectively). Age, gender, race, education, and income were not statistically significant independent predictors of utility scores.Conclusion In a sample of the general population and medical students, utility assessments for living with unilateral mastectomy were comparable with those of living with bilateral mastectomy and severe breast hypertrophy. Our sample population, if faced living with unilateral mastectomy was willing to gamble a theoretical 14% chance of death and willing to trade 4.2 years of existing life-years.
Keywords: utility assessment; quality-adjusted life years; unilateral mastectomy; breast reconstruction